Money and happiness: Evidence from the industry wage structure - Jörn-Steffen Pischke (Institute for the Study of Labor (IZA), 2011)
There is a well-established positive correlation between life-satisfaction measures and income in individual level cross-sectional data. This paper attempts to provide some evidence on whether this correlation reflects causality running from money to happiness. I use industry wage differentials as instruments for income. This is based on the idea that at least part of these differentials are due to rents, and part of the pattern of industry affiliations of individuals is random. To probe the validity of these assumptions, I compare estimates for life satisfaction with those for job satisfaction, present fixed effects estimates, and present estimates for married women using their husbands' industry as the instrument. All these specifications paint a fairly uniform picture across three different data sets. IV estimates are similar to the OLS estimates suggesting that most of the association of income and well-being is causal.
urn:nbn:de:101:1-201105306284
Keywords: D1; J31; 330; life satisfaction; well-being